Development of the Tampa Scale of Kinesiophobia for Parkinson's disease: confirmatory factor analysis, reliability, validity and sensitivity to change. Issue 2 (June 2015) - Monticone, Marco; Ferrante, Simona; Ambrosini, Emilia; Rocca, Barbara; Secci, Claudio; Foti, Calogero
Abstract : The aim of this study was to validate the Tampa Scale of Kinesiophobia for Parkinson's disease (TSK-PD). This was a cross-sectional evaluation of the psychometric properties of an adapted questionnaire. The psychometric testing included confirmatory factor analysis, reliability by internal consistency (Cronbach's α ) and test–retest reliability (intraclass correlation coefficient), construct validity by comparing TSK-PD with the Falls Efficacy Scale-International (FES-I), the Movement Disorder Society – Unified Parkinson's Disease Rating Scale (MDS-UPDRS), the Hospital Anxiety and Depression Score (HADS) and the Short-Form Health Survey (SF-36) (Pearson's correlations), and sensitivity to change by calculating the smallest detectable change. The questionnaire was administered to 132 patients with Parkinson's disease. Factor analysis confirmed a two-factor (harm and activity avoidance), 13-item solution, which led to an acceptable data-model fit. Internal consistency ( α =0.94) and test–retest reliability (intraclass correlation coefficient, model 2.1=0.90) were good. Construct validity showed a close correlation between the TSK-PD and FES-I ( r =−0.710); a moderate correlation with the MDS-UPDRS ( r =0.513); moderate to close correlations with HADS-D ( r =0.443) and HADS-A ( r =0.626); moderate correlations with the mental subscales of the SF-36 ( r =−0.327 to −0.563); and poor correlations with the physical subscales of the SF-36 ( r =−0.236 to −0.248). The smallest detectable change was 11. The TSK-PD had a good factorial structure and satisfactory psychometric properties. Its use is recommended for clinical and research purposes.